Clinically meaningful change threshold in health‐related quality of life among patients aged 6 months to 5 years with atopic dermatitis and their caregiver(s)/family - Amy S. Paller; Servando E. Marron; Diane Whalley; Lauren Nelson; Shanshan Qin; Jingdong Chao; Ashish Bansal; Chien‐Chia Chuang; Zhixiao Wang (Wiley, 2024)
Abstract Background Atopic dermatitis (AD) significantly impacts health‐related quality of life (HRQoL) in children and their caregiver(s)/family. Measures to assess HRQoL include the Children's Dermatology Life Quality Index (CDLQI), Infants' Dermatitis Quality of Life Index (IDQoL) and Dermatitis Family Impact (DFI) questionnaire. Currently, there are no established clinically meaningful within‐person change thresholds for these measures in young children (6 months to 5 years) and their caregiver(s)/family. Objectives To determine the clinically meaningful within‐person change thresholds for CDLQI (4-5 years), IDQoL (<4 years) and DFI scores in children aged 6 months to 5 years with moderate‐to‐severe AD and their caregiver(s)/family. Methods Data from the 16‐week, randomised, double‐blind, placebo‐controlled, phase 3 LIBERTY AD PRESCHOOL part B study in children aged 6 months to 5 years were used. The anchor‐based method was used to assess meaningful change thresholds for the three instruments, using the Caregiver Global Impression of Disease (CGID; range: 'no symptoms' to 'very severe') as the primary anchor, and Caregiver Global Impression of Change (CGIC; range: 'much better' to 'much worse') as a supportive anchor. Results The mean CDLQI change scores were −6.3 and −9.5 based on CGID 1‐point improvement and CGIC improvement of 'a little better', respectively. The mean IDQoL change scores were −5.6 and −3.4 based on the CGID and CGIC anchors. The mean DFI change scores were −7.0 and −6.7 based on the CGID and CGIC anchors. Conclusions Based on primary anchor findings, improvements of ≥6 points on the CDLQI total score for children aged 4-5 years and on the IDQoL total score for children aged <4 years were recommended as the clinically meaningful within‐person change thresholds in children with moderate‐to‐severe AD. A 7‐point improvement on the DFI total score may be considered as the meaningful threshold for the caregiver(s)/family of children aged 6 months to 5 years with moderate‐to‐severe AD.